Negotiating Conflicts of Needs in Designing Teaching English for Midwifery Students - Sujana, I Made; Hanafi, Nurachman; Wilian, Sudirman; Syahrial, Edy; Fitriana, Eka (Universitas Negeri Makassar, 2019)
As an international lingua franca, English plays an important role for students of health for both academic and career success; however, it is often neglected in its planning and implementation. The present study aims at redesigning the teaching of English for midwifery students using an ESP approach by analyzing present situations (PSA), target situations (TSA), and learning situations (LSA) as the basis for designing English programs. The research was conducted at Midwifery Department, Polytechnic of Health (Politeknik Kesehatan henceforth POLTEKES) Mataram, Indonesia involving students, English lecturers, subject specialists, and management. Data were collected using triangulation techniques – ECSCS Test, questionnaires, interviews, Focus Group Discussion (FGD), and documentation â€“ and were analyzed qualitatively and quantitatively based on the characteristics of data. The research found that (i) the studentsâ€™ level of English was still low (84.6% in Basic); (ii) the target needs (necessities) are to be able to communicate both spoken and written in carrying out the duties in workplaces and professional development; (iii) from those results mentioned above, there were conflicts among aspects of needs in designing courses, that is, the high target does not correspond to entry behavior, the number of credits allocated, and facilities. Considering the results of NA, it is suggested that the English programs can be designed using Necessities (TSA)-based Approach, PSA-based Approach, or Mixed Approach with its own advantages and disadvantages